Réponses

2014-05-28T12:49:20+02:00
A= 3(2x + 8)                        B= 3x² -1                             C= x² + 2xy + y²                   
A= 3(2*2/3 + 8) -7                 B= 3*(2/3)² -1                       C= (2/3)² + 2*2/3*3 + 3² 
A= 3(4/3 + 8 ) -7                   B= 3*4/9 -1                          C= 4/9 + 12/3 + 9
A= 3*4/3 + 3*8 -7                  B= 12/9 -1                           C= 4/9 + 12*3/3*3 + 9 
A= 12/3 + 24 -7                     B= 12/9 -1*9/1*9                  C= 4/9 + 36/9 + 9
A=12/3 + 24*3/1*3 -7             B= 12/9 -9/9                         C= 4+36/9 + 9
A= 12/3 + 72/3 -7                  B= 12-9/9                             C= 40/9 + 9
A= 12 +72/3 -7                      B= 3/9=1/3                           C= 40/9 + 9*9/1*9
A= 84/3 -7                                                                        C= 40/9 + 81/9
A= 84/3 -7*3/3*1                                                                C= 40 + 81/9
A= 84/3 -21/3                                                                     C= 121/9
A= 84-21/3
A= 63/3 = 21